TOKSISITAS DAN IMUNOGENISITAS PRODUK EKSTRASELULER Streptococcus agalactiae TIPE NON-HEMOLITIK PADA IKAN NILA (Oreochromis niloticus ) - Sefti Heza Dwinanti; Sukenda .; Munti Yuhana; Angela M Lusiastuti (Universitas Sriwijaya, 2014)
ABSTRACT The aim of this research was to analyse the toxicity and immunogenicity of ECP of non-hemolytic S. agalactiae and to evaluate ECP as a material vaccine for prevention of S. agalactiae. Toxicity to tilapia was detected in the ECP. There was a chronic mortality pattern which was shown after post ECP injection. By intraperitoneal injection into young tilapia (± 20 g), the median lethal dose were calculated at 633,9 µg/kg bodyweight for isolate 3 and 685,4 µg/kg bodyweight for isolate 5. Cytopathic effects of ECP to tilapia’s lymphocytes were observed during 0, 30, 60 and 180 minutes. A mixture of ECP caused nuclear granulation and cytoplasmic streaming after 60 minutes. Using immunodiffusion analysis, precipitate line was demonstrated against tilapia anti-ECP sera, and there was bio-specific type anti sera against for each isolate. The ECP vaccine effective to protect tilapia from S. agalactiae was injected intraperitoneally (IP) at 2 x 105 CFU/ml. Tilapia vaccinated with ECP from isolat 3 which protein 283 µg/kg bodyweight had a RPS value 60%. Tilapia vaccinated with ECP from isolat 5 which protein 408 µg/kg had a RPS value 68%. Keywords: toxicity, immunogenicity, extracellular products, Streptococcus agalactiae, tilapia